Use of Lexan Petri-type long dishes instead of growth tubes for "clock" mutants - M. D. Berliner; P. W. Neurath (Fungal Genetics Reports, 1965)
Use of Lexan Petri-type long dishes instead of growth tubes for "clock" mutants